MUHAMMED YÛSUF EL-BENNÛRÎ'NİN HADİSÇİLİĞİ VE ŞERH YÖNTEMİ (MEÂRİFÜ'S-SÜNEN ÖZELİNDE) - YÜKSEL, FATİH MUHAMMET (Fırat Üniveristesi, 2024)
Modern dönemde ortaya çıkan oryantalistlerin, hadise dair görüşlerinden en çok etkilenen bölgelerin başında Hint coğrafyası gelmektedir. Aynı zaman diliminde İngiliz işgal ve sömürüsüne maruz kalan bölge, bu yolla batı dünyasındaki düşünce ve fikir akımlarıyla da tanışmıştır. Mamafih mezkûr coğrafyada Ekber Şah döneminden itibaren izlenen siyasette İslam'a karşı farklı tezahürlerle karşılaşılmıştır. Mezkûr sebepler, hususiyetle hadis ilminde umumiyetle de İslam ilimlerinin hepsinde farklı ekollerin, farklı yaklaşımların oluşmasına zemin hazırlamıştır. Bu özelliğiyle Hint alt kıtası, dünya Müslümanlarının karşılaştıkları problemleri tespit açısından önemli bir merkezdir. Hindistan-Pakistan coğrafyasında Hanefiliği temsil eden ekollerden en önemlisi Diyobend Ekolü'dür. Ekol, kurumsal çalışmaları, yetiştirdiği kalifiye insan portresi, burada yetişen âlimlerin telif, tahkik, tercüme gibi birçok alanda ilim dünyasına yaptığı katkıyla temayüz etmiştir. Bundan dolayı hem kendi bölgesinde hem de dünya çapında adını duyurmayı başarmış, hatta markalaşmış bir kurum hüviyetini kazanmıştır. Pakistan'ın ayrılmasıyla birlikte Hindistan'ın iki farklı ülkeye bölünmesi neticesinde Diyobend Ekolüne mensup bazı âlimler Hindistan'da kalmayı tercih ederken diğer bazıları Pakistan'a geçip faaliyetlerini orada sürdürme kararı almıştır. Pakistan'a hicret etmeyi tercih eden isimlerden birisi de Muhammed Yûsuf el-Bennûrî'dir. Diyobend'in önemli isimleri Enver Şah el-Keşmîrî ve Şebbîr Ahmed el-Osmânî gibi isimlerden ders almış olan el-Bennûrî her ne kadar ülkemizde yeterince tanınmıyor olsa da İslam âleminin farklı ilim çevrelerinde tanınan bir şahsiyettir. Hem Hanefî hem de hadisçi olması ve ilim camiasında adından söz ettirmesi, şahsiyet ve fikriyatını araştırmanın doğal gerekçesini oluşturmaktadır. Bu çalışmada; el-Bennûrî'nin hayatı, eserleri, hadisçiliği ve şerh metodu ele alınmıştır. Böylece son dönemde Hint alt kıtasında yetişen, çalışmalarıyla doğru orantılı olarak ilim dünyasında adından söz ettiren el-Bennûrî'nin Türk akademik camiasına özellikle hadis sahasında faaliyet icra eden araştırmacılara tanıtılması amaçlanmıştır.

The geography of India is one of the most influenced regions by the views of Orientalists emerged in the modern era, particularly in relation to the subject of hadith. The region, which was subjected to British occupation and exploitation, became aware of the movements of thoughts and ideas in the western world in this way. However, in the aforementioned region, various manifestations against Islam have been encountered in the politics since Akbar Shah period. These reasons have paved the way for the formation of different movements and approaches, spesicifally in the science of hadith and generally in all of the Islamic sciences. Consequently, the Indian subcontinent is a pivotal center in determining the challenges faced by the Muslims all around the world. The most important school representing Hanafi school in Indo-Pak region is the Deoband Movement. This movement has distinguished itself with its corporate work, the portrait of qualified people it has trained, the contributions of the scholars trained in this school to the scholarly community in many fields such as writing, critical edition and translation. Accordingly, it has succeeded in making its name both in its own region and worldwide and even gained the identity of a branded institution. As a result of the separation of Pakistan from India, some scholars of Deoband school preferred to remain in India, while some others decided to migrate to Pakistan and continue their activities there. Among those who preferred to migrate to Pakistan is Muhammad Yousuf Banuri. al-Banuri, who studied under important scholars of Deoband such as Anwar Shah Kashmiri and Shabbir Ahmad al-Usmani, is a person known in different scholarly communities of the Islamic world, although he is not well-known in our country. The fact that he is both Hanafi and a hadith scholar and that he has made a name for himself in the scientific community constitutes the natural justification for researching his personality and ideas. In this study, life and works of al-Banuri, his position in hadith science and his commentary method have been examined. Thus, it is aimed to introduce al-Banuri, who recently grew up in the Indian subcontinent and left an indelible mark with his works, to the Turkish academic community, particularly researchers studying in the field of hadith.
Hadith understanding and commentary method of Muhammad Yousuf al-Bannuri (The case of Maarif al-Sunan)
Keywords: Din